Discovery of Fluidic LiBH4 on Scaffold Surfaces and Its Application for Fast Co-confinement of LiBH4-Ca(BH4)(2) into Mesopores - Lee, Hyun-Sook; Hwang, Son-Jong; To, Magnus; Lee, Young-Su; Cho, Young Whan (American Chemical Society, 2015)
Generation of fluidic LiBH4 molecules, f-LiBH4, was demonstrated by NMR spectroscopy of LiBH4 bulk powder Mixed with silica scaffold surface materials under minor heat treatment. In the presence of the fumed scaffold mesoporous MCM-41 and SBA-15, LiBH4 shows increased translational mobility at relatively low temperature (ca. 95 degrees C) and becomes liquid-like by evidence from H-1-B-11 J-coupling in H-1 and B-11 MAS NMR or substantial line narrowing of Li-2 static NMR This high diffusional mobility of LiBH4 at the molecular level has never been seen for bulk LiBH4, and the property is attributed to the interfacial interaction with the mesoporous scaffold surfaces. While f-LiBH4 facilitates the confinement of LiBH4 itself into various scaffold materials, LiBH4 migrates along the SBA-15 surface to reach other metal borohydride particles, Ca(BH4)(2) in this case, and promotes the formation of similarly fluidic LiBH4-Ca(BH4)(2) composite (LC solid solution) for coconfinement into mesopores. In situ variable temperature (VT) NMR spectroscopy detects the co-infiltration process of eutectic LiBH4-Ca(BH4)(2) composite (LC) into mesopores of SBA-15. The infiltration rates measured for LiBH4 bulk powder or LC composite showed dependence on pore sizes (MCM-41 vs SBA-15) and heat treatment conditions (static vs MAS).
Keywords: SOLID-STATE NMR; HYDROGEN RELEASE; NANOCONFINED LIBH4; CARBON; REVERSIBILITY; DECOMPOSITION; SILICA; BH4; NANOPARTICLES; DESORPTION